A recepção de Shakespeare na Alemanha - Borgato, Rafhae [UINESP]l; Maas, Wilma Patricia Marzari Dinardo [UNESP] (My University, 2011)
This is an article about a decisive moment in the formation of Western modern literature. We are talking about Lessing’s criticism of the excessive influence of neoclassical French theatre on German theatrical production. Lessing considered that the aristocratic model imported from France did not correspond to German society’s context at all – society which had already been marked by an incipient bourgeois mode of life. So the German critic dedicated his theoretical efforts to affirm the necessity and to raise possibilities about a literary production which had more consonance with what he considered to be the German Zeitgeist. It is in Shakespeare’s work that Lessing found his answer, and this fact will unleash the appearing of the Sturm und Drang movement and will consequently give birth to an incipient bourgeois literature. So we analyze here the way this Shakespearian influence happens and its relevance in the formation of a bourgeois literature.

Este artigo trata de um momento decisivo para a formação da literatura moderna ocidental. Referimo-nos à crítica de Lessing à influência exacerbada do teatro neoclássico francês na produção teatral alemã. Lessing considerava que o modelo aristocrático importado da França em nada correspondia ao contexto da sociedade alemã, já marcada por um incipiente modo de vida burguês. Sendo assim, o crítico dedica seu esforço teórico a afirmar a necessidade e levantar possibilidades sobre um fazer literário que estivesse em maior consonância com o que ele considerava ser o espírito alemão. É na obra de Shakespeare que Lessing encontra sua resposta, fato que desencadeará o surgimento do movimento Sturm und Drang e, consequentemente, trará à luz uma literatura burguesa incipiente. Analisamos aqui, então, como se dá essa influência shakespeariana e sua importância na formação de uma literatura de cunho burguês.
Shakespeare's Reception in Germany
Keywords: Lessing; Shakespeare; Literary Modernity; Sturm und Drang; French Neoclassicism; German Literature; Lessing; Shakespeare; Modernidade Literária; Sturm und Drang; Neoclassicismo francês; Literatura Alemã